2021
DOI: 10.31687/saremnms.21.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of a maned sloth (Bradypus torquatus Illiger, 1811) by a tiger shark (Galeocerdo cuvier Péron and LeSueur, 1822) in southeastern Brazil

Abstract: We present the first record of maned sloth (Bradypus torquatus) consumption by the tiger shark (Galeocerdo cuvier). Our record is based on the analysis of stomach contents of a tiger shark captured off the coast of Rio de Janeiro state, southeastern Brazil. Although it is not possible to distinguish between a predation and scavenging event, we consider it likely that the sloth was consumed while dispersing between the islands of the region. We also comment on the heretofore unforeseen risks of aquatic dispersa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Furthermore, tiger sharks were also observed feeding on dead whales in Abrolhos in another study, responsible for 54% of all bites found on carcasses ( Bornatowski et al, 2012b ). Interestingly, the first record concerning the predation of a sloth by a tiger shark was obtained for the South Atlantic, in the state of Rio de Janeiro ( Miranda & Santos, 2021 ), although whether the sloth was preyed on when moving between local islands or if the carcass reached the sea and was then consumed post-mortem could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tiger sharks were also observed feeding on dead whales in Abrolhos in another study, responsible for 54% of all bites found on carcasses ( Bornatowski et al, 2012b ). Interestingly, the first record concerning the predation of a sloth by a tiger shark was obtained for the South Atlantic, in the state of Rio de Janeiro ( Miranda & Santos, 2021 ), although whether the sloth was preyed on when moving between local islands or if the carcass reached the sea and was then consumed post-mortem could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…It exhibits a circumglobal distribution, inhabiting tropical and temperate waters in all oceans [ 25 ], and, similarly to many other sharks from an ecosystem point of view, it plays an essential role as a trophic regulator of ecosystem interaction networks [ 26 ]. Tiger sharks exhibit a very varied diet, composed of a wide variety of marine and terrestrial organisms, in addition to carcasses [ 27 , 28 , 29 ]. The species is ovoviviparous and exhibits a high fecundity, producing between 10 and 82 neonates per posture [ 30 ], although it is late to mature, reaching maturity between seven (males) and eight (females) years old [ 31 ].…”
Section: Introductionmentioning
confidence: 99%